SEED YIELD AND QUALITY INDICATORS OF THE “OTAVNIY” SAINFOIN CULTIVAR UNDER DIFFERENT ECOLOGICAL CONDITIONS - Djamolova U.; Rabbimov A. (The Bioscan, 2024)
This article presents data on the growth, development, individual seed yield, and seed quality of the “Otavniy” sainfoin cultivar, a desert forage plant species, under various ecological conditions.